2009
DOI: 10.1001/archpediatrics.2008.507
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Palsy, Autism Spectrum Disorders, and Developmental Delay in Children Born After Assisted Conception

Abstract: To assess the existing evidence of associations between assisted conception and cerebral palsy (CP), autism spectrum disorders (ASD), and developmental delay. Data Sources: Forty-one studies identified in a systematical PubMed and Excerpta Medica Database (EMBASE) search for articles published from January 1, 1996, to April 1, 2008. Study Selection: Studies written in English comparing children born after assisted conception with children born after natural conception assessing CP, ASD, and developmental delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
92
3
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 77 publications
(154 reference statements)
4
92
3
9
Order By: Relevance
“…[4][5][6] ART is reported to double the risk of CP overall. 7 This is likely related to the increased proportions of preterm and multiple births, both risk factors for CP. 1 However, there is variation across studies regarding singletons, who comprise 88% of all cases of CP in Australia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] ART is reported to double the risk of CP overall. 7 This is likely related to the increased proportions of preterm and multiple births, both risk factors for CP. 1 However, there is variation across studies regarding singletons, who comprise 88% of all cases of CP in Australia.…”
mentioning
confidence: 99%
“…1 However, there is variation across studies regarding singletons, who comprise 88% of all cases of CP in Australia. 1 Some studies report that the risk of CP is doubled for singletons born after in vitro fertilization (IVF), 7,8 while others have found no increased risk in this group. [9][10][11] The risk of CP for multiple births is well established and studies have reported that ART conception does not further increase risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies (10,18,21) reported an association between assisted conception and CP, whereas others could not demonstrate such statistical significance (6,14,32). According to the regression analysis, the risk of CP in IVF children is largely attributed to a high proportion of multiple pregnancies, low birth weight, and prematurity in this population (6,14,21,25,41). The selected studies showed inconsistent findings as some found an association between CP and IVF singletons (18,21) and others did not (6,14,25,27,34).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, assessment of the risk of neurodevelopmental disorders at older ages, such as dyslexia or fine manipulative dyspraxia was excluded. In systematic review published by Hvidtjørn et al (41), the main focus was on the assessing of associations between ART and CP. This study was based on the original data and articles published from January 1, 1996 to April 1, 2008 with a follow-up of 1 year or more.…”
Section: Discussionmentioning
confidence: 99%